Obtención de parámetros óptimos en la operación de flotación por aire disuelto. - Fernández-Rangel, Ditter; Suárez-Padrón, Adriana; Díaz-Díaz, Miguel; Rivas-Trasancos, Lester; Cañete-Pérez, Carlos C.; Romero-Silva, Roberto; Teuteló-Nuñez, Raíza; Miller-Palmer, Sandra; Maza-Pineda, Nora La (Revista CENIC Ciencias Quimicas, 2015)
The dissolved air flotation systems (DAF) are wisely used for the treatment wastewater of the petroleum industry. To design a DAF system it is necessary to obtain the main operation parameters in the lab scale. In the present work the DAF system´s optimum parameters for the depuration of oil wastewater were determined. A response surface procedure with central composite design was applied. The pressure in the pressurized tank, residence time in the flotation chamber and the percentage of recycle were the independient variables, while the response variables were remotion of chemical oxygen demand (COD) and oil content. First a flocculation process was applied to the wastewater before to pass to the flotation test. The removals obtained fluctuate between 22,6 % and 97,3 % for the hydrocarbons and 12 % and 41 % for the COD. The optimal parameters for the system are: 32 % for recycle, 385,03 kPa of pressure in the pressurized tank and 13 min for the time in the flotation chamber.